2013
DOI: 10.1007/s00264-013-2034-y
|View full text |Cite
|
Sign up to set email alerts
|

Semitendinosus tendon regeneration after anterior cruciate ligament reconstruction: can we use it twice?

Abstract: Purpose It has been demonstrated that the semitendinosus tendon can regenerate after being harvested in its whole length and thickness for anterior cruciate ligament (ACL) reconstruction. Ultrasound studies and guided biopsies of the regenerated tendon have shown compatibility and resembling features of the normal tendon. The question is if this neo-tendon is biologically and functionally adequate for re-use? Methods Two randomised groups of 150 volunteers were followed up for two years after harvesting the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 28 publications
0
22
0
1
Order By: Relevance
“…The data reported in these studies are conflicting (16)(17). Stevanović et al investigated regeneration at the hamstrings donor site after ACLR using clinical and ultrasound examination, biopsies and histological tests (18). The investigators demonstrated regeneration in 72% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…The data reported in these studies are conflicting (16)(17). Stevanović et al investigated regeneration at the hamstrings donor site after ACLR using clinical and ultrasound examination, biopsies and histological tests (18). The investigators demonstrated regeneration in 72% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…It has adequate power, it is easily taken and easily placed to adequate position. At the moment, 4-strand hamstring tendon graft is the most used graft with this surgery -it has adequate power, it is easily placed and there are no bigger complications of donor's place [35][36][37] . More important than the graft choice is the graft position, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 It has recently been suggested that the regenerated hamstrings tendons appear to have similar structure as the tendons in the non-harvested side. 2 Most studies that have investigated knee flexion strength recovery after ACLR with a hamstrings graft on isokinetic devices (typically in a seated position) found that there are no residual strength deficits [5][6][7][8] even though patients frequently describe perceived weakness. To explain this paradox, recent research has suggested that knee flexion strength should be measured in deep knee flexion angles where the deficits are more obvious.…”
Section: Introductionmentioning
confidence: 99%